Morphometry of different instars larvae of the poplar leaf miner (Phyllonorycter populifoliella (Treitschke, 1833)) - Sinchuk, Nadzeya V. (Experimental Biology and Biotechnology, 2023)
Poplars (Populus spp.) are common in the green areas in Belarus. They are damaged by a wide range of phytophagous insects. The poplar leaf miner (Phyllonorycter populifoliella (Treitschke, 1833)) is a species of Gracillariidae (Lepidoptera) regularly having population outbreaks. The one is a dangerous pest of poplars in the green areas of Belarus. Ph. populifoliella larvae live within spot mines on the leaf blades of poplars, mass colonisation of foliage leads to early defoliation. Detailed morphometric data makes possible to identify larvae instars, which is important for understanding of the species’ phenology and planning population management measures. The conducted research provided data on the morphometry of Ph. populifoliella larvae at all instars based on several parameters: body length, width of the head capsule, width of the 1st–3rd thoracic segments and width of the 1st–3rd abdominal segments. Using the one-way analysis of variance (ANOVA) method and Tukey’s post hoc test in Python, the statistical significance of differences between larvae of five age groups across all considered parameters has been confirmed with the possibility of using morphometric data to identify the instars of poplar leaf miner larvae – a dangerous pest of poplars in the green areas of Belarus.